2013
DOI: 10.1590/s0101-20612013000400030
|View full text |Cite
|
Sign up to set email alerts
|

Phisicochemical, sensory, and microbiological evaluation and development of symbiotic fermented drink

Abstract: The goal of this study was to develop a symbiotic lacteous drink, evaluate its physicochemical and sensory characteristics, and verify the viability of Lactobacillus acidophilus in the drink. The milk serum-based drink consisted of 50% milk serum containing 10% saccharose, 25% powdered milk, 15% yacon pulp, and cultures of Lactobacillus acidophilus-La 5E and Bifidobacterium bifidum BB12. It was stored for up to 21 days under refrigeration. The milk serum-based drink was analyzed for protein, ether extract, tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 19 publications
3
9
0
Order By: Relevance
“…In the present study, the changes observed for the texture determined instrumentally in the desserts during storage did not interfere in the acceptability of these products. Some studies show that the sensory characteristics of dairy products with probiotic lactobacilli is mainly affected by their acidity [ 48 , 49 , 50 ]. In the study by Buriti et al [ 48 ], it was found by preference test that fresh cream cheese with the addition of Lactobacillus paracasei LBC82 in co-culture with S. thermophilus TA40 showed a more acidic taste and was significantly less preferred over the control, with only S thermophilus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, the changes observed for the texture determined instrumentally in the desserts during storage did not interfere in the acceptability of these products. Some studies show that the sensory characteristics of dairy products with probiotic lactobacilli is mainly affected by their acidity [ 48 , 49 , 50 ]. In the study by Buriti et al [ 48 ], it was found by preference test that fresh cream cheese with the addition of Lactobacillus paracasei LBC82 in co-culture with S. thermophilus TA40 showed a more acidic taste and was significantly less preferred over the control, with only S thermophilus.…”
Section: Discussionmentioning
confidence: 99%
“…The highest averages obtained by these authors were for yogurts without probiotics (between 6.5 and 7.5). In turn, the study by Dias et al [ 50 ] when evaluating the acceptability values of a synbiotic fermented dairy beverage with addition of L. acidophilus LA-5 using the nine-point hedonic scale, showed changes throughout storage, although considered good, since between zero and seven days of storage the mean scores were close to 5.0 (equivalent to “neither like nor dislike”), which increased significantly between 14 and 21 days ( p < 0.05), reaching values close to 6.0 (equivalent to “slightly like”), also in attribution to the increase of the acidity.…”
Section: Discussionmentioning
confidence: 99%
“…The development of the technology of whey-based beverages is examined in [12][13][14][15][16][17][18][19][20][21][22][23].…”
Section: Research Of Existing Solutions Of the Problemmentioning
confidence: 99%
“…The authors [17] develop a symbiotic milk beverage consisting of 50 % milk whey, 10 % sucrose, 25 % milk powder, 15 % cellulose from the yakon and cultures Lactobacillus acidophilus -La 5E and Bifidobacterium bifidumBb12. The physicochemical and sensory characteristics of the beverage are evaluated.…”
Section: Research Of Existing Solutions Of the Problemmentioning
confidence: 99%
See 1 more Smart Citation